GAGASAN PENGEMBANGAN PONDOK PESANTREN AL-FALAH MENURUT PEMIKIRAN MUHAMMAD TSANI - Abdullah Husin (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2009)
This paper tries to map Muhammad Tsani Thought on Pondok Pesantren, with the case of Pondok Pesantren Al Falah, in facing the changing current. According to Muhammad Tsani, Pesantren must be able to play the role at least in two aspects: firstly, in closed or limited area at pondok pesantren its self, that pondok pesantren suggested to have a good quality of product. Secondly, pondok pesantren hoped to have the social role that related with the society need. Usually, both of the two aspects known with the term of ilmu and amal. Actually, this basic paradigm is the main capital of pondok pesantren to face the modernity challenges and to play its main role as the moral counter.